Pengaruh Gaya Kepemimpinan, Motivasi Kerja Dan Manajemen Waktu Terhadap Kinerja Karyawan (Studi pada CV. Bina Reka Sub Kontraktor Lamongan) - M. Risqi Roynaldi; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted at CV. Lamongan Sub-Contractor Development. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of leadership style, work motivation and time management on employee performance. The independent variables used are leadership style, work motivation and time management, while the dependent variable is employee performance. The sample used in this study were 49 respondents who were employees of CV. Lamongan Sub-Contractor Development. Data collection techniques using a questionnaire. The analytical method used is instrument test, multiple linear regression analysis, classical assumption test, determination test, f test and t test using SPSS 16.0 computer software for data processing. The results of this study indicate that leadership style affects employee performance, work motivation affects employee performance, time management affects purchasing decisions. Leadership style, work motivation and time management simultaneously affect employee performance. Keywords: Leadership Style, Work Motivation, Time Management And Employee Performance.